When Ghosts Come Home : a novel - Cash, Wiley (New York, NY : William Morrow, an imprint of HarperCollins Publishers, 2021)
"The eagerly awaited novel from the New York Times bestselling author of A Land More Kind Than Home, a tender and haunting story of a father and daughter, crime and forgiveness, race and memory"--.
Keywords: Sheriffs -- North Carolina -- Fiction; Aircraft accidents -- Investigation -- Fiction; Murder -- Investigation -- Fiction; Race relations -- Fiction; Fathers and daughters -- Fiction; Suspense fiction